2010
DOI: 10.1007/s00894-010-0697-5
|View full text |Cite
|
Sign up to set email alerts
|

A leucine-rich repeat assembly approach for homology modeling of the human TLR5-10 and mouse TLR11-13 ectodomains

Abstract: So far, 13 groups of mammalian Toll-like receptors (TLRs) have been identified. Most TLRs have been shown to recognize pathogen-associated molecular patterns from a wide range of invading agents and initiate both innate and adaptive immune responses. The TLR ectodomains are composed of varying numbers and types of leucine-rich repeats (LRRs). As the crystal structures are currently missing for most TLR ligand-binding ectodomains, homology modeling enables first predictions of their three-dimensional structures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 33 publications
2
31
0
1
Order By: Relevance
“…The Toll-like receptors (TLRs) are a class of pattern recognition receptors that recognize pathogen-associated molecular patterns (PAMPs), as well as play a critical role in the innate immune response to invading pathogens [1][2][3][4]. TLR9 is activated by DNA from invasive bacteria and by synthetic oligodeoxynucleotides (ODNs) containing unmethylated cytosine-phosphate-guanosine (CpG) motifs [5].…”
Section: Introductionmentioning
confidence: 99%
“…The Toll-like receptors (TLRs) are a class of pattern recognition receptors that recognize pathogen-associated molecular patterns (PAMPs), as well as play a critical role in the innate immune response to invading pathogens [1][2][3][4]. TLR9 is activated by DNA from invasive bacteria and by synthetic oligodeoxynucleotides (ODNs) containing unmethylated cytosine-phosphate-guanosine (CpG) motifs [5].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is believed that human LC express functional TLRs, which are more active to stimulation with TLR2, 3, 7 and 8 ligands. 38 In vitro studies with other fungi or yeast, such as C. albicans, have shown that TLR2 recognizes the glycopeptide phospholipmannan on the surface of the cell wall of the micro-organism and TLR4 recognizes the polysaccharide mannan, also on the fungal cell wall. 43,44 That is, the expression of TLR2 and TLR4 in keratinocytes is important for the host defense against C. albicans.…”
Section: Toll-like Receptorsmentioning
confidence: 99%
“…39 Several studies have proved that these receptors are functional and participate in immune responses. 38,39 In vitro studies found that the supernatant from keratinocytes stimulated via TLR3 may stimulate immature DC derived from monocytes toward cell differentiation and, consequently, production of TNFα and type I IFNγ (type I interferon gamma), developing Th1 cell responses from wild-type T cells. 40 This indicates that keratinocytes can direct Th1-type adaptive immune responses.…”
Section: Toll-like Receptorsmentioning
confidence: 99%
See 2 more Smart Citations